The Right to Access the Internet and Modern Models of Digital Discrimination - E. L. Sidorenko; N. Yu. Molchakov (Сравнительная политика, 2024)
The article proposes a systematic assessment of the right to the Internet in the context of modern legal and political challenges. The authors substantiate the thesis that the right to the Internet is a complex category that cannot be considered solely in terms of providing technical capabilities and overcoming the digital divide (inequality) between different social groups and states. Much more complex and important is the consideration of the right to the Internet in the context of the corresponding duty of states not to impede the possibility of information exchange via the Internet, as well as in the plane of the search for a “golden mean” between the right to the Internet and natural human rights.The main purpose of the article was to determine the main features of the right to the Internet in the context of human and civil rights and freedoms and to analyze the main manifestations of digital discrimination as a consequence of the digital divide.A detailed methodological basis of the article contributed to the achievement of the abovementioned purpose. The research was based on a systematic method, which made it possible to consider the right to the Internet as a complex and dynamically developing legal and political category. The authors used functional and logical (deduction, induction and analogy) methods, as well as a number of particular scientific methods: historical, sociological and statistical. The approach proposed in the article to determine the key parameters of the right to the Internet was substantiated mainly on the basis of the application of comparative legal, formal legal and axiological methods.The methodology of the research made it possible to formulate and substantiate the conclusion that the right to the Internet in the face of modern legal and political challenges is undergoing a qualitative transformation both in the direction of expanding the positive obligations of the state to overcome the digital divide, and in the direction of restricting the right to freedom of Internet communication under the auspices of ensuring the right to privacy and the need to respect the public interest. The presence of «double standards» in determining the boundaries of the right to the Internet leads to conflicting legal decisions and allows us to predict the aggravation of this contradiction in the context of the rapid development of digital platforms and the active sanction policy of the collective West.